2012
DOI: 10.1016/s2221-1691(13)60011-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal activity of Atalantia monophylla (L) Correa against Spodoptera litura Fab. (Lepidoptera: Noctuidae)

Abstract: As per our knowledge, this is the first report for ovicidal activity of A. monophylla against S. litura, A. monophylla could be used for the management of S. litura and other insect pests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…It was shown that the chemical compounds present in these Piperaceae can be further evaluated among the isolation of active molecules to develop new botanical formulations, especially when we consider that the majority of these substances has been reported as potential insecticides in many other studies conducted worldwide (Santos et al, 2010;2013;Cáceres & Kato, 2014, Brito, Baldin, Silva, Ribeiro, & Vendramim, 2015Krinski & Foerster, 2016, Sanini et al 2017, Turchen, Hunhoff, Paulo,Souza, Pereira, 2016b and other plant families (Isman, 2000;Koul, Walia, & Dhaliwal, 2008;Tripathi, Upadhyay, Bhuiyan, & Bhattacharya, 2009;Coitinho, Oliveira, Gondim-Júnior, & Câmara, 2010;Ntalli & Menkissoglu-Spiroudi, 2011, Zoubiri & Baaliouamer, 2011Baskar, Muthu, Raj, Kingsley, & Ignacimuthu, 2012;Krishnappa & Elumalai, 2012;Cáceres & Kato, 2014Krinski, Massaroli, & Machado, 2014;Backiyaraj et al, 2015;Massaroli, Pereira, & Foerster;Costa, Santana, Oliveira, & Serrão, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the chemical compounds present in these Piperaceae can be further evaluated among the isolation of active molecules to develop new botanical formulations, especially when we consider that the majority of these substances has been reported as potential insecticides in many other studies conducted worldwide (Santos et al, 2010;2013;Cáceres & Kato, 2014, Brito, Baldin, Silva, Ribeiro, & Vendramim, 2015Krinski & Foerster, 2016, Sanini et al 2017, Turchen, Hunhoff, Paulo,Souza, Pereira, 2016b and other plant families (Isman, 2000;Koul, Walia, & Dhaliwal, 2008;Tripathi, Upadhyay, Bhuiyan, & Bhattacharya, 2009;Coitinho, Oliveira, Gondim-Júnior, & Câmara, 2010;Ntalli & Menkissoglu-Spiroudi, 2011, Zoubiri & Baaliouamer, 2011Baskar, Muthu, Raj, Kingsley, & Ignacimuthu, 2012;Krishnappa & Elumalai, 2012;Cáceres & Kato, 2014Krinski, Massaroli, & Machado, 2014;Backiyaraj et al, 2015;Massaroli, Pereira, & Foerster;Costa, Santana, Oliveira, & Serrão, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Larva is the most destructive stage of S. litura in which attacked leaves and pods that plays an important role in the early reproductive phases. The presence of this insects pest should be considered because its known to have many host plants including cultivated plant and wild plant [2], [6], [7]. This pest was known to have ability to develop multiple type of resistance rapidly against chemical insecticide due to its short life cycle and the intensive use of the product [8]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…This pest is native to Asia but has been spread worldwide in many host plants (Baskar et al 2012). S. litura attacks soybean leaves and pods which play an important role in the early reproductive phases thus resulted in crop failure.…”
Section: Introductionmentioning
confidence: 99%